Efectuati:
Răspunsuri la întrebare
Răspuns de
1
[ x ·( 2x -1) + 2 ·( 2x + 1) - 3x -1 ] / ( 4x² -1) =
= [ 2x² -x + 4x + 2 -3x -1 ] / ( 4x² -1) =
= [ 2x² + 1 ] / ( 2x -1 ) ·( 2x +1)
= [ 2x² -x + 4x + 2 -3x -1 ] / ( 4x² -1) =
= [ 2x² + 1 ] / ( 2x -1 ) ·( 2x +1)
Răspuns de
0
Alte întrebări interesante
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Ed. muzicală,
9 ani în urmă